The Role of Health Cadres in Promoting Child Vaccination in Areas with Low Education Levels - Lamsir, Seno (Oshada, 2025)
Background: Disparities in basic childhood immunization coverage remain evident in communities with low education levels, often associated with limited health literacy, vaccine hesitancy, and barriers to accessing health services. In this context, the role of health cadres is considered crucial in supporting childhood vaccination uptake at the community level. Method: This study employed a quantitative cross-sectional design involving 210 mothers with children aged 12–24 months. Data were collected using structured questionnaires and analyzed through binary logistic regression to examine the influence of health cadres’ roles on the completeness of basic childhood vaccination. Results: The findings indicate that health cadres’ roles significantly influenced complete basic vaccination (OR = 3.08; p = 0.001) after controlling for maternal education and socioeconomic status. Schedule reminders and interpersonal communication emerged as the strongest dimensions of the cadres’ role, while assistance during vaccination visits showed the weakest contribution due to logistical constraints. Conclusion: The results demonstrate that achieving complete childhood vaccination depends not only on formal health system mechanisms but also on strengthening the role of health cadres as social and educational agents within the community. Enhancing persuasive communication skills, improving logistical support, and integrating cadres into community-based follow-up systems are essential to ensure sustainable improvements in basic childhood vaccination coverage.